Enhancement patterns of gastric carcinoma on contrast-enhanced ultrasonography: relationship with clinicopathological features. - Fang Wei (Public Library of Science (PLoS), 2013)
The aim of this study was to assess the relationship between the enhancement patterns and clinicopathological features of gastric cancer using intravenous contrast-enhanced ultrasonography (CEUS). In this Ethics Committee-approved prospective study, five hundred fifty two patients with gastric cancer who gave informed consent were examined preoperatively with CEUS. The enhancement pattern of each tumor was analyzed visually. Gross and histopathological findings on the postoperative specimens were compared with the preoperative CEUS findings. The most common CEUS pattern in differentiated gastric cancer was homogeneous enhancement, whereas heterogeneous enhancement was the most common pattern in undifferentiated gastric cancer. The proportion of heterogeneous enhancement was significantly different between the two histological subtypes (Chi- square = 146.735, P<0.001). The sensitivity and specificity of early heterogeneous enhancement on CEUS in diagnosing undifferentiated gastric cancer were 78.84% and 72.59% respectively. Gastric cancers with heterogeneous enhancement were more often Borrmann III and IV macroscopic types than those with homogeneous enhancement (66.56% vs. 30.80%, P<0.001), more commonly T3 and T4 depth of invasion than those with homogeneous enhancement (71.52% vs. 59.60%, P<0.05), more often showed lymphatic invasion than those with homogeneous enhancement (84.44% vs. 76.40%, P<0.05), and were less likely to receive curative gastrectomy than those with homogeneous enhancement (74.83% vs. 86.40%, P<0.005). The intra- and inter-observer reproducibility were both almost perfect for assessing enhancement patterns, with Kappa values of 0.916 (P<0.001) for intra-observer and 0.842 (P<0.001) for inter-observer reproducibility. CEUS provided detailed information about tumor vascularity and contrast enhancement patterns in gastric cancer. CEUS is promising as a new and useful method to predict the histological type of gastric cancer.